2013
DOI: 10.1080/08964289.2013.799452
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Cervical Cancer Screening Intentions among Latinas Using An Expanded Theory of Planned Behavior Model

Abstract: We examined the utility of an expanded Theory of Planned Behavior (TPB) model in predicting cervical cancer screening intentions among Latinas. The model included acculturation and past cervical cancer screening behavior along with attitude, subjective norms, and perceived behavioral control. This cross-sectional study included a sample of 206 Latinas who responded to a self-administered survey. Structural equation modeling was employed to test the expanded TPB model. Acculturation (p= .025) and past screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 31 publications
10
33
1
Order By: Relevance
“…Our findings are consistent with studies that have employed components of the TPB to predict cervical cancer screening in other female populations (Jennings-Dozier, 1999; Fernbach, 2002; Sheeran & Orbell, 2000) and studies employing the TPB to predict screening intentions in Latinas (Roncancio et al, 2013). We found that perceived behavioral control was the strongest predictor of intention such that women with higher perceived behavioral control expressed greater intentions to be screened for cervical cancer.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are consistent with studies that have employed components of the TPB to predict cervical cancer screening in other female populations (Jennings-Dozier, 1999; Fernbach, 2002; Sheeran & Orbell, 2000) and studies employing the TPB to predict screening intentions in Latinas (Roncancio et al, 2013). We found that perceived behavioral control was the strongest predictor of intention such that women with higher perceived behavioral control expressed greater intentions to be screened for cervical cancer.…”
Section: Discussionsupporting
confidence: 90%
“…The TPB suggests, "All external factors, such as demographics, or personality characteristics of the actor, the nature of particular behavior under investigations, or situational variables can affect intentions only if they influence the attitudinal or normative components or their relative weights" [29]. On the other hand, this result was in line with previous TPB-based studies which revealed no significant effect of sociodemographic characteristics on the intention to screen for cervical cancer [30].…”
Section: Discussionsupporting
confidence: 83%
“…The PBC measures correlated significantly (r = −.246, p < .001). Cronbach's alpha for the product items is rather low (α = .68), which is not surprising as it is already reported in several studies that PBC scales tend to have a low internal reliability (Askelson et al, 2010;Grunfeld, & Kohli, 2010;Klöckner & Matthies, 2009;Roncancio, Ward, & Fernandez, 2013). "Self-efficacy" was also rated on a six-point Likert-type scale with each respondent indicating their confidence to overcome each barrier (1 = not at all confident to 6 = very confident).…”
Section: Pbc and Self-efficacymentioning
confidence: 54%